Plataforma de teste de Gateway Lora para IoT baseada em SDR - Silva, João Paulo Silvino Belo da (2023)
Currently, the massive presence of smart devices connected to the internet is a reality. Since the beginning of the current century, when the Internet of Things (IoT) emerged, different data transmission and management technologies have been developed and improved, in order to provide more efficient solutions for the various fields of application. This context allowed the use of LPWAN (Low-Power Wide-Area Network). This wireless network type is characterized by the data transmission over long distances with low energy consumption, important característics of IoT. In this group, the LoRaWAN protocol stands out, which has a flexible structure, allowing the user to independently build and parameterize their network or use a cloud computing service, which can be public or private. In addition, it has considerable acceptance and use, motivating a wide variety of equipment on the global market. In this work, it was sought to develop a tests platform to evaluate the performance of different models of LoRaWAN gateways, a fundamental device in this type of network, which operates by transferring the information sent by the end devices (nodes) to a cloud server, as well as acting in the opposite direction. Considering the different types of interference in communication between end devices and gateways in commercial LoRaWAN networks, it was implemented a platform composed of an emulated end devices. Therefore, it is possible to transmit specifications LoRaWAN compatible signals, by a software defined radio (SDR). The transmission parameters settings and adding noise to signals transmitted by emulated end devices allowed the creation of scenarios that simulate the characteristics and possible interferences on a LoRaWAN network. The performance of the devices was established from the analysis of the reception capacity of signals transmitted through a software-defined radio (SDR), and based on the technical specifications of the protocol. Experimental results show the best gateway considering the applied test stimulus.